2018
DOI: 10.1039/c7dt04608a
|View full text |Cite
|
Sign up to set email alerts
|

A helical chain-like organic–inorganic hybrid arsenotungstate with color-tunable photoluminescence

Abstract: A 1-D infinite helical chain-like organic-inorganic hybrid arsenotungstate NaH[{Pr(HO)}{AsWO}{WO(mal)}]·24HO (mal = malate) (1) was prepared, which was characterized by elemental analyses, thermogravimetric (TG) analyses, IR spectroscopy, powder X-ray diffraction (PXRD) and X-ray single-crystal diffraction. Structural characterization revealed that 1 comprises the organo-functionalized [{AsWO}{WO(mal)}] polyanions hinged together by the Pr ions forming a 1-D infinite helical chain-like architecture. The malate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Structural characterization of Na 4 H 8 [{Pr(H 2 O) 2 } 2 {As 2 W 19 O 68 }{WO 2 (mal)} 2 ]·24H 2 O revealed that the Pr III ions formed a 1D infinite helical chain-like architecture by hinging between organo-functionalized [{As 2 W 19 O 68 }{WO 2 (mal)} 2 ] 18− polyanions. In this case, mal ligands stabilized the structure by the formation of five-membered W–O–C–C–O chelate rings [ 133 ].…”
Section: Inorganic–organic Hybrids Based On Respsmentioning
confidence: 99%
“…Structural characterization of Na 4 H 8 [{Pr(H 2 O) 2 } 2 {As 2 W 19 O 68 }{WO 2 (mal)} 2 ]·24H 2 O revealed that the Pr III ions formed a 1D infinite helical chain-like architecture by hinging between organo-functionalized [{As 2 W 19 O 68 }{WO 2 (mal)} 2 ] 18− polyanions. In this case, mal ligands stabilized the structure by the formation of five-membered W–O–C–C–O chelate rings [ 133 ].…”
Section: Inorganic–organic Hybrids Based On Respsmentioning
confidence: 99%
“…Recently, the rational design and synthesis of novel coordination polymer materials based on polyoxometalates (POMs) have attracted significant attention due to their intriguing structures and potential applications in electrochemistry, magnetism and catalysis. [1][2][3][4][5][6][7] However, there are relatively fewer applications in the field of proton conduction. 8 POMs, in fact, have irreplaceable advantages in proton conduction, due to their high Brønsted acidity and oxygen-rich surfaces, and as a material with abundant metaloxygen clusters, can serve as proton donors or carriers to form multiple hydrogen-bonding networks.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs), as a class of nanosized discrete anionic metal-oxide clusters, have drawn enormous attention and are applied widely in many fields (e.g., magnetism, medicine, electrochemistry, and especially in catalysis) because of their unique physicochemical properties. In recent years, many researchers have demonstrated POM-based catalysts did have praiseworthy catalytic performance for selective oxidation of DPM to BP. However, POMs suffer from some intrinsic drawbacks, including low specific surface area, high water solubility, and difficult separation (reuse), which shackle the further industrial applications of POMs. ,, Therefore, a promising solution is to select a proper carrier and load the POMs . Simultaneously, metal–organic frameworks (MOFs), which have tunable nanospaces providing satisfactory accommodation for multitudinous guest species, have been regarded as a new class of porous materials. Thanks to their inherent tunability, MOFs have cumulative application in gas storage, magnetism, fluorescence, and catalysis.…”
Section: Introductionmentioning
confidence: 99%